Level of awareness on halal food among Muslim food retailers in Jalan Hang Tuah, Melaka / Noor Emma Lina Muhamad - Muhamad, Noor Emma Lina (Faculty of Business and Management, 2018)
Intense competition in the business of foods industry forces Muslim retailers to look for their best approach to attract and create a halal food to their customers. However some of retailers take an easy action in operating their restaurants which can be create issues to Muslim customers sensitivity. This research focused on the level of awareness among Muslim food retailers to know the factors that contribute to it. The factors that contributed in level of awareness of halal foods are halal exposure, religious beliefs, health reasons and role of halal certification and logo. All the Muslim foods retailers used Muslim as opportunity to their business firms to make customers to believe that they always aware with halal or they have a high level of awareness. The main study of this research is to examine the relationship between factors that contributes to the level of awareness with the level of awareness among Muslim food retailers. Halal awareness being dependent variables in this research and measured by four independent variables which is halal exposure, religious beliefs, health reasons and role of halal of certification and logo. The literature review confirms this relationship. This research is based on 70 respondents which survey is collected from Muslim food retailers who are operated their business in 1 kilometer from Jalan Hang Tuah, Melaka. Sampling method used in this study is simple random sampling. The data was analyzed using correlation coefficient and regression by using SPSS software. The findings reveal that are positive relationship between all the factors with the level of awareness on halal foods. However, the result shows that halal exposure has most influential factors towards halal awareness.